Emergence of a dalbavancin induced glycopeptide/lipoglycopeptide non-susceptible Staphylococcus aureus during treatment of a cardiac device-related endocarditis. Issue 1 (December 2018) - Kussmann, Manuel; Karer, Matthias; Obermueller, Markus; Schmidt, Katy; Barousch, Wolfgang; Moser, Doris; Nehr, Marion; Ramharter, Michael; Poeppl, Wolfgang; Makristathis, Athanasios; Winkler, Stefan; Thalhammer, Florian; et al.
Abstract In the present study, we demonstrated the emergence of dalbavancin non-susceptible and teicoplanin-resistantStaphylococcus aureus small colony variants which were selected in vivo through long-term treatment with dalbavancin. A 36-year-old man presented with a cardiac device-relatedS. aureus endocarditis and received long-term therapy with dalbavancin. Consecutively, two glycopeptide/lipoglycopeptide susceptible and two non-susceptibleS. aureus isolates were obtained from blood cultures and the explanted pacemaker wire. The isolates were characterized by: standard typing methods, antimicrobial susceptibility testing, auxotrophic profiling, proliferation assays, scanning and transmission electron microscopy, as well as whole genome sequencing. The isolated SCVs demonstrated a vancomycin-susceptible but dalbavancin non-susceptible and teicoplanin-resistant phenotype whereof the respective MICs of the last isolate were 16- and 84-fold higher than the susceptible strains. All four strains were indistinguishable or at least closely related by standard typing methods (spa, MLST, and PFGE), and whole genome sequencing revealed only eight sequence variants. A consecutive increase in cell wall thickness (up to 2.1-fold), an impaired cell separation with incomplete or multiple cross walls and significantly reduced growth rates were observed in the present study. Therefore, the mutations inpbp2 and the DHH domain of GdpP were identified as the most probable candidates due to their implication in the biosynthesis and metabolism of the staphylococcal cell wall. For the first time, we demonstrated in vivo induced dalbavancin non-susceptible/teicoplanin resistant, but vancomycin and daptomycin susceptibleS. aureus SCVs without lipopeptide or glycopeptide pretreatment, thus, indicating the emergence of a novel lipoglycopeptide resistance mechanism.